HIGH HEPARANASE LEVEL IN SURVIVORS OF COVID-19 — INDICATOR OF VASCULAR AND PULMONARY RECOVERY?. Issue 6 (31st December 2022) - Neb, Holger; Talbot, Steven R.; Ruskowski, Katharina; Brkic, Djurdjina; Sonntagbauer, Michael; Adam, Elisabeth H.; von Knethen, Andreas; Zacharowski, Kai; Heinicke, Ulrike
ABSTRACT: Background: Severe progression of coronavirus disease 2019 (COVID-19) causes respiratory failure and critical illness. Recently, COVID-19 has been associated with heparanase (HPSE)-induced endothelial barrier dysfunction and inflammation, so called endothelitis, and therapeutic treatment with heparin or low-molecular-weight heparin (LMWH) targeting HPSE has been postulated. Because, up to this date, clinicians are unable to measure the severity of endothelitis, which can lead to multiorgan failure and concomitant death, we investigated plasma levels of HPSE and heparin-binding protein (HBP) in COVID-19 intensive care patients to render a possible link between endothelitis and these plasma parameters. Therefore, a prospective prolonged cohort study was conducted, including 47 COVID-19 patients from the intensive care unit. Plasma levels of HPSE, and HBP were measured daily by enzyme-linked immunosorbent assay in survivors (n = 35) and nonsurvivors (n = 12) of COVID-19 from admission until discharge or death. All patients were either treated with heparin or LMWH, aiming for an activated partial thromboplastin time of ≥60 seconds or an anti-Xa level of >0.8 IU/mL using enoxaparin, depending on the clinical status of the patient (patients with extracorporeal membrane oxygenation or >0.1 μg/kg/min noradrenaline received heparin, all others enoxaparin). Results: We found significantly higher plasma levels of HPSE and HBP in survivors and nonsurvivors of COVID-19, compared with healthy controls. Still, interestingly, plasma HPSE levels were significantly higher ( P < 0.001) in survivors compared with nonsurvivors of COVID-19. In contrast, plasma HBP levels were significantly reduced ( P < 0.001) in survivors compared with nonsurvivors of COVID-19. Furthermore, when patients received heparin, they had significantly lower HPSE ( P = 2.22 e − 16) and significantly higher HBP ( P = 0.00013) plasma levels as when they received LMWH. Conclusion: Our results demonstrated that patients, who recover from COVID-19–induced vascular and pulmonary damage and were discharged from the intensive care unit, have significantly higher plasma HPSE level than patients who succumb to COVID-19. Therefore, HPSE is not suitable as marker for disease severity in COVID-19 but maybe as marker for patient's recovery. In addition, patients receiving therapeutic heparin treatment displayed significantly lower heparanse plasma level than upon therapeutic treatment with LMWH.